Analysis of Stock Price Forecasting With ARIMA Method - Rahman, Arif; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Nowadays, lot of people make an investments to get a passive income. This is used by many companies to acquire financial resources through the stock offering to society. However, the stock is a type of investment that has the potential for greater gains and losses than other types of investment. This happens because of the difficulty of predicting the change of stock prices that. To be able to predict the stock prices fluctuated, it needed a forecast of stock price in the future. One of the method that can be used to forecast is the Box-Jenkins ARIMA method. Based on trial and forecasting evaluation, it is known that, this analysis produces the best ARIMA model that can be used to forecasting the next five periods, so it can help the society to determine the best ARIMA model in forecasting the stock price of several companies. Best ARIMA models for forecasting the stock prices of EXCL is ARIMA (1,1,0) with MAPE 1.2472%, to forecasting the stock prices of FREN is ARIMA (0,1,1) with MAPE 1.0749%, to forecasting the stock prices of ISAT is ARIMA (1,2,2) with MAPE 4.9396%, and to forecasting the stock prices of TLKM is ARIMA (1,1,1) with MAPE 1.0045%.